Síntese hidrotérmica assistida por micro-ondas de tiO2, e aplicação em nanocompósito - Tavares, Mara Tatiane de Souza (2013)
In recent decades have seen a sharp growth in the study area of nanoscience and nanotechnology and is included in this area, the study of nanocomposites with self-cleaning properties. Since titanium dioxide (TiO2) has high photocatalytic activity and also antimicrobial, self-cleaning surfaces in your application has been explored. In this study a comparison was made between two synthesis routes to obtain TiO2 nanoparticles by hydrothermal method assisted by microwave. And after analysis of XRD and SEM was considered the best material for use in nanocomposites. It was deposited nanocomposite film of poly (dimethyl siloxane) (PDMS) with 0.5, 1, 1.5 and 2% by weight of nanoparticles of titanium dioxide (TiO2) by the spraying method. The nanocomposite was diluted with hexane and the suspension was deposited onto glass substrate, followed by curing in an oven with forced air circulation. The photocatalytic activity of the nanocomposite impregnated with methylene blue was evaluated by UV- vis spectroscopy from the intensity variation of absorption main peak at 660nm with time of exposure to the UV chamber. Changes in the contact angle and microhardness were analyzed before and after UV aging test. The effect of ultraviolet radiation on the chemical structure of the PDMS matrix was evaluated by spectrophotometry Fourier transform infrared (FTIR).The results indicated that the addition of TiO2 nanoparticles in the coating PDMS gave high photocatalytic activity in the decomposition of methylene blue, an important characteristic for the development of self-cleaning coatings